Kekuatan Hukum Perjanjian Sewa Menyewa Dihadapan Notaris - Suta Ramadan; Dodi Setiawan; Rian Setiawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Law has an important role in regulating human actions, creating balance in society. In Indonesia, law is divided into public law and civil law, where the law of engagement is included in civil law. Leases, as part of the engagement, are governed by Article 1548 BW, and according to R. Subekti, constitute a consensual contractual agreement. In the context of a lease agreement, its legal force can be analyzed when it is made before a notary. This study uses a qualitative approach with a descriptive method to analyze the legal strength of a lease agreement before a notary. The discussion involved Article 1320 of the Civil Code, which provides freedom to make written agreements without the involvement of a notary. The results showed that the lease agreement can be made in the form of a notarial deed or under hand. Notary deeds provide high evidentiary power because they are considered undeniable evidence of their existence and content. However, underhand agreements can also be used as evidence by being acknowledged by the parties involved.